Utilization of the Folk Story “Marsikam” as History Learning Material to Develop the Values of Unity and Cooperation among Students - Ihut Marasi Pakpahan; Hendra; Ridwin Purba; Asne Surbakti; Resmi (Bulletin of Pedagogical Research, 2025)
This research aims to examine the utilization of the "Marsikam" folktale as historical learning material in fostering unity and cooperation values among students. The "Marsikam" folktale was chosen because it contains moral messages and noble values relevant to the social life context of society, particularly unity and cooperation values. The research method used is qualitative with a literature study approach and content analysis. Data were obtained from the "Marsikam" script and secondary sources related to historical learning and character education. The research results show that the "Marsikam" story can be integrated into historical learning material as an effective learning medium to instill unity and cooperation values. Through analysis of characters, plot, and conflict in the story, students can understand the importance of solidarity, tolerance, and collaboration in facing social challenges. The implementation of the "Marsikam" story in historical learning can also increase active student engagement and build awareness of the importance of maintaining unity in diversity. This research recommends the use of folktales as an alternative creative and contextual learning material to strengthen character education in schools.